Utilizing Cultural Inclusivity as an Attraction to Increase Commercial Games' Locals and Foreign Players - Wijaya, Fenie Fedora; Elizabeth, Gracelyn; Wardaya, Marina (Universitas Ciputra, 2025)
This study analyses the role of cultural representation in the attractiveness of video games to both domestic and foreign audiences. This study also wants to fills a gap by examining how cultural representation in video games influences player engagement and market appeal, an area often overlooked in game design research. The scope of this analysis includes Genshin Impact and Coral Island, which are representative of Chinese and Indonesian culture, respectively. This research uses a mixed method with a quantitative approach through a survey of 46 respondents and a qualitative approach through interviews and focus group discussions (FGDs) with 12 participants from Indonesia, Taiwan and Paraguay. Incorporating different cultural perspectives, the scope of this study aims to analyze how inclusivity and cultural representation in games can increase game appeal and player loyalty and expand market reach. The findings of this study are expected to assist game producers in building the appropriate strategies in integrating cultural elements to increase competitiveness in the global market.